Optimization of training for professional rugby union players: investigating the impact of different small-sided games models on GPS-derived performance metrics - Ren, X.; Henry, M.; Boisbluche, S.; Philippe, K.; Demy, M.; Ding, S.; Prioux, J. (Frontiers in Physiology, 2024)
Introduction Professional rugby union players can improve their performance by engaging in small-sided games (SSGs), which simulate the movement patterns of the game. This study collected metrics related to running performance and mechanical workload and their relative values from both forward and back positions, aiming to explore the impact of different SSGs factors on athlete workload, as well as the workload difference between official games (OGs) and SSGs.